LIPID PROFILE IN DETERMINATION OF PROSTATIC PATIENT - THANA ISMAIL MUSTAFA (مجلة جامعة الانبار للعلوم الصرفة, 2012)
This study was included investigation the effects of prostate gland on lipid metabolism and other parameters Blood sample were collected from (37) male patient ( (20) cancer prostate ,(17) with benign prostate hypertrophy ) and (25) from control serum prostate specific antigen (PSA) was determined by Enzyme linked immunoabsorbent assay (ELISA method) ,C.R.Protein by agglutination test and lipid profile include (total cholesterol, triglycerides, high density lipoprotein(HDL), Low density lipoprotein(LDL), Very low density lipoprotein (VLDL) and Risk factors were done.The result showed the value of TPSA,CRP,T.cholesterol,Triglycerides and risk factors increase significantly in patient group compard to control group , while HDL value decrease in patient group. The result of this study explain the relation ship between the incrase of TPSA and risk factor which lead to arterosclerosis in men .